2015
DOI: 10.1167/iovs.14-16223
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Coping on Vision-Related Quality of Life in Patients With Low Vision: A Prospective Longitudinal Study

Abstract: Our findings showed that avoidant coping has a detrimental impact on VRQoL over time. Low vision specialists should be aware of their patients' coping strategies and encourage them to engage in active rather than avoidant coping to deal with the impact of their vision impairment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
25
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 40 publications
7
25
1
1
Order By: Relevance
“…Other psychosocial variables such as negative and positive coping were demonstrated to be the significant determinant of HRQoL at 6 months follow-up which was partly consistent with Sturrock's findings [45]. In their study, only avoidant coping not acceptance coping was observed to significantly determined decline in visionrelated functioning.…”
Section: Discussionsupporting
confidence: 83%
“…Other psychosocial variables such as negative and positive coping were demonstrated to be the significant determinant of HRQoL at 6 months follow-up which was partly consistent with Sturrock's findings [45]. In their study, only avoidant coping not acceptance coping was observed to significantly determined decline in visionrelated functioning.…”
Section: Discussionsupporting
confidence: 83%
“…Other psychosocial variables, such as negative and positive coping, were demonstrated to be signi cant determinants of HRQoL at the 6month follow-up, which was partly consistent with Sturrock's ndings [45]. In their study, only avoidance coping, not acceptance coping, was observed to signi cantly determine a decline in vision-related functioning.…”
Section: Discussionsupporting
confidence: 79%
“…In a study conducted in low vision population in Australia, a significant impact of coping strategies on vision-related QoL has been reported. 27 Similar to low vision, refractive error is generally a chronic stressor warranting a need of examining a direct relationship between coping strategies and refractive QoL.…”
mentioning
confidence: 99%